The Relationship between Leisure Time Physical Activity and High-risk Behaviors with Mediating Personality among the Students of University of Isfahan - Ahmadali Asefi; Hossein Mohebiniya (فصلنامه رفاه اجتماعی, 2023)
Introduction The aim of this study was to investigate the relationship between leisure physical activity and high-risk behaviors with personality mediating role in students of University of Isfahan.